(untitled) (JOISCO: Journal of Islamic Communication, 2026)
The era of digital disruption has shifted the paradigm of communication in West Kalimantan, marked by the transfer of information authority from newsrooms to global digital platform algorithms. This condition has triggered the phenomenon of post-truth and information overload, which has implications for the erosion of the role of local mainstream media as guardians of public ethics and gatekeepers of credible information. This study aims to analyze the factors causing the weakening of the role of local mainstream media in West Kalimantan and to formulate an ethical reorientation model based on communication principles in the Qur’an as a preventive measure against social damage (al-fasād). The study uses a descriptive qualitative method with a literature study and Tafsir Maudhu’i (thematic) approach. Primary data was obtained from the text of the Qur’an and authoritative tafsir books, while secondary data came from contemporary media theory and observation of local media phenomena. Data analysis was conducted using content analysis techniques to synthesize the reality of media practices with Islamic normative values. The results of the study indicate the erosion of the role of mainstream media, characterized by the dominance of algorithms over editorial policies, the speed of news production that trumps accuracy, audience fragmentation through filter bubbles, and the commodification of news